The conceptual regulations of resourcesaving activities of agrarian enterprises - Кузьменко, О. Б. (Scientific Progress & Innovations, 2012)
The article substantiates the need to develop resource-saving activities of agrarian enterprises with the use of innovative technologies of «organic» farming. The conceptual regulations of such development are proposed. They comprise: preconditions and factors of resource-saving activities of enterprises, the main goals of resource-saving activities, evaluation of system of resource utilization of agrarian enterprises, mechanisms for the implementation of conceptual regulations, target areas and the main tasks of resource-saving activities; expected results.